Effects of tachyplesin on proliferation and differentiation of human hepatocellular carcinoma SMMC-7721 cells - Ouyang, Gao-Liang (World J Gastroenterol, 2002)
AIM: To investigate the antitumor activities of tachyplesin on human hepatocellular carcinoma (HCC) cells. METHODS: Tachyplesin, isolated from acid extracts of Chinese horseshoe crab (Tachypleus tridentatus) hemocytes, was used to treat the human HCC cell line SMMC-7721. Effects of tachyplesin on the proliferation of SMMC-7721 cells were measured with trypan blue dye exclusion test and HE staining. The morphology and ultrastructure of the cells were examined by light microscopy and transmission electron microscopy, respectively. The activities of γ-glutamyltransferase (γ-GT) and tyrosine aminotransferase (TAT) were assayed with biochemical methods. The levels of alpha fetoprotein (α-FP), proliferating cell nuclear antigen (PCNA), p21(WAF1/CIP1) and c-myc were examined by immunocytochemistry. RESULTS: After treatment with tachyplesin 3.0 mg/L, the proliferation of SMMC-7721 cells was inhibited significantly, with the cell growth inhibitory rate amounted to 55.57% and the maximum cell mitotic index declined by 43.68%. The morphology and ultrastructure underwent restorational alteration. The activity of γ-GT declined while TAT activity increased obviously, and the levels of α-FP and PCNA decreased. Moreover, the expression of p21(WAF1/CIP1) protein was up-regulated and that of c-myc protein was down-regulated. CONCLUSION: Tachyplesin could effectively inhibit the proliferation of hepatocarcinoma cells, reverse the malignant morphological and ultrastructural characteristics, alter the levels of enzymes and antigens, regulate the expression of differentiation-associated oncogene and tumor suppressor gene, and induce hepatocarcinama cell differentiation.